The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jmft.12417
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Divide: Couple and Family Therapy Programs’ Integration of Teletherapy Training and Education

Abstract: The mental health field is increasingly integrating and growing a teletherapy presence, and couple and family therapists are uniquely situated to offer these services based on our history of innovative approaches to therapeutic services. To do so successfully, careful consideration of training and education must occur. To evaluate current teletherapy training and education opportunities of COAMFTE accredited couple, marriage, and family therapy programs, an inductive qualitative content analysis was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 25 publications
1
52
0
5
Order By: Relevance
“…While these results provide specific and important findings regarding the barriers and ways student therapists overcame the barriers associated with providing relationally based telemental health, additional research is needed to verify these results. There is also need for additional research that can identify the systemic educational barriers training programs may be facing when incorporating relationally based telemental health principles and practices in their programs (Pickens et al, 2019). Finally, and more importantly we need more research on the clients' experiences of receiving and benefitting from relationally based telemental health treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these results provide specific and important findings regarding the barriers and ways student therapists overcame the barriers associated with providing relationally based telemental health, additional research is needed to verify these results. There is also need for additional research that can identify the systemic educational barriers training programs may be facing when incorporating relationally based telemental health principles and practices in their programs (Pickens et al, 2019). Finally, and more importantly we need more research on the clients' experiences of receiving and benefitting from relationally based telemental health treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hertlein et al (2015) found that over 85% of the MFTs they sampled reported that they were somewhat interested in learning about web‐based services. Pickens et al (2019) evaluated the degree to which family therapy training programs provide training in telemental health. They found that while more than two thirds of those responding were in favor of integrating telemental health within their programs, most were not addressing it at all within their curriculum.…”
mentioning
confidence: 99%
“…Em atenção a essa demanda emergente, no Brasil, o Conselho Federal de Psicologia (CFP) regulamentou a expansão dos serviços psicológicos prestados por meio das tecnologias da informação e da comunicação (TICs) durante a pandemia (Conselho Federal de Psicologia, 2020a). Não obstante, questões complexas sobre atendimentos remotos têm sido levantadas, sobretudo por terapeutas de casal e família, os quais, até então, vinham realizando seu trabalho quase exclusivamente na modalidade presencial (Lebow, 2020;Pickens, Morris, & Johnson, 2020). Essas questões incluem aspectos técnicos e éticos, com destaque a como engajar os membros da família via videoconferência, evitar distrações no ambiente doméstico, adaptar intervenções que envolvam crianças pequenas e garantir a privacidade dos membros da família que estão em atendimento frente àqueles que não estão (Lebow, 2020;Wade et al, 2020).…”
Section: Terapia De Parejas Y Familias On Lineunclassified
“…As fragilidades na formação em terapia on-line com casais e famílias se associam também a dúvidas quanto a indicações e contraindicações dessa modalidade, inclusive entre profissionais com experiência em terapia on-line individual (Wrape & McGinn, 2019). Assim, capacitações profissionais e supervisões têm se mostrado relevantes para a qualificação da terapia on-line com casais e famílias (Pickens et al, 2020), podendo ser realizadas por meio das TICs (Borcsa & Pomini, 2018;Pennington, Patton, Ray, & Katafiasz, 2017).…”
Section: Terapia De Parejas Y Familias On Lineunclassified
See 1 more Smart Citation